Generalized tetanus in an eight-year-old girl: a case report - Yimenicioğlu, Sevgi; Turhan, Sevil; Saglam, Celal; Bildirici, Yaşar; Akdemir, Bekir (The European Research Journal, 2022)
Tetanus, a vaccine-preventable disease threatens life. Tetanus has four clinical presentations: neonatal, localized, cephalic, and generalized. Generalized tetanus was the most common presenting feature on admission to the hospital. We report a case with generalized tetanus with difficulty swallowing and sore throat by admission. She was eight years old. She had symptoms on the fifth day of nail soak. She rapidly developed an opisthotonic posture on the first day of admission. She was discharged on foot on the seventieth day. Generalized tetanus should be kept in mind that a patient may be admitted to a hospital with difficulty swallowing and a sore throat.